2010
DOI: 10.1055/s-0030-1250149
|View full text |Cite
|
Sign up to set email alerts
|

Subjektive Krankheitstheorien und funktionaler Verlauf nach Knie- und Hüftgelenkersatz

Abstract: The results confirmed the prognostic relevance of illness perceptions for the functional outcome and indicate the importance of preoperative counselling and the potential benefit of patient-oriented education that is aimed at modifying illness perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Table 1 shows that 14 studies (40 %) had low risk of bias for the follow-up domain. Eight studies [ 14 21 ] had a high risk of bias on this domain. One study [ 22 ] had a loss to follow-up of >20 % in the first and third year, but a low loss to follow-up at 5 and 7 years, so that risk of bias was unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows that 14 studies (40 %) had low risk of bias for the follow-up domain. Eight studies [ 14 21 ] had a high risk of bias on this domain. One study [ 22 ] had a loss to follow-up of >20 % in the first and third year, but a low loss to follow-up at 5 and 7 years, so that risk of bias was unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Two included high risk of bias studies (6 %) reported an association between patient expectations and outcomes. Bethge et al [ 14 ] found that patients who expected an enduring illness and did not expect treatment to be helpful had worse postoperative scores on the HHS. Judge et al [ 18 ] showed that patients with high expectations were more likely to improve on the WOMAC scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very important aspect remained unaddressed: Asking patients about their own beliefs and concepts of sickness, health and the origin of their disease as well as asking about complementary medicine and “self-treatment”. This whole area was not covered in the included literature, despite there being strong evidence that this can be an important part of recovery [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study, preoperative illness-related concern was found to be associated with poorer functional outcome 1 year after TKA (Bethge et al. 2010). There was a correlation between a higher degree of distress and lower use of problem-focused coping strategies (Folkman and Moskowitz 2004), which may in turn result in avoidance of activity.…”
Section: Discussionmentioning
confidence: 99%